Phylogenetic relationships within the genus holothuria inferred from 16S mitochondiral rRNA gene sequences - Kamarudin K.R.; Rehan A.M.; Hashim R.; Usup G.; Rehan M.M. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by WOS/Scopus